2013
DOI: 10.1159/000356209
|View full text |Cite
|
Sign up to set email alerts
|

De novo Reciprocal Translocation t(5;6)(q13;q34) in Cattle: Cytogenetic and Molecular Characterization

Abstract: The cytogenetic analysis of a phenotypically normal bull from the Marchigiana breed revealed the presence of an abnormal karyotype due to the presence of a very long chromosome. This finding, identified in all the metaphases observed, was associated with the 2n = 60, XY karyotype, suggesting the presence of a reciprocal translocation. RBG- banding analyses identified a de novo reciprocal translocation involving BTA5 and BTA6, t(5;6)(q13;q34), while FISH analyses using cattle-specific BACs as probes enabled the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Recently, a method using a panel of subtelomeric FISH-probes on a multihybridization device, as a means of highlighting the ends of each chromosome, has also been applied to cattle chromosomes to detect structural chromosome abnormalities [153]. However, only two studies extended the analyses using the CGH array to establish possible genetic material losses during chromosome rearrangements (Table 7) [16,149]. At least in these two latter cases, no genetic losses occurred during the rearrangements.…”
Section: Reciprocal Translocationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a method using a panel of subtelomeric FISH-probes on a multihybridization device, as a means of highlighting the ends of each chromosome, has also been applied to cattle chromosomes to detect structural chromosome abnormalities [153]. However, only two studies extended the analyses using the CGH array to establish possible genetic material losses during chromosome rearrangements (Table 7) [16,149]. At least in these two latter cases, no genetic losses occurred during the rearrangements.…”
Section: Reciprocal Translocationsmentioning
confidence: 99%
“…Chromosome abnormalities can also be easily spread by offspring, especially when using artificial insemination, with adverse economic effects on animal breeding. The advent of chromosome-banding and FISH-mapping techniques with specific molecular markers (generally BAC clones), reviewed by [13], as well as chromosome painting probes (Zoo-FISH) [14,15], the use of CGH arrays [16], and the availability of standard chromosome nomenclatures [17], have led to the development of powerful tools for cytogeneticists in their daily work. With these tools, they can identify the chromosomes involved in abnormalities and the possible loss or gain of genetic material (especially using CGH arrays).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, heterozygotes for several different reciprocal translocations have been detected in Bos taurus (Iannuzzi et al ., ; De Lorenzi et al ., , , ; Molteni et al ., ; Switonski et al ., ; Perucatti et al ., ) and in the water buffalo, Bubalus bubalis (Di Meo et al ., ), but these appear to be rare and have important detrimental effects on the carrier's fertility, and the viability of progeny (Switonski & Stranzinger, ). Some very rare autosomal translocations were described in horses that presented normal phenotypes but were apparently subfertile (Lear & Bailey, ).…”
Section: Chromosomal Rearrangements Associated With Polymorphisms In mentioning
confidence: 99%
“…FISH experiments were performed according to the protocol described by De Lorenzi et al (2014). The BACs used as probes belonged to the INRA Library (Eggen et al 2001) and are reported in Table 1.…”
Section: Fluorescent In Situ Hybridization (Fish)mentioning
confidence: 99%